Barriers Impeding Postgraduate Training Completion and Dissertation Submission and Defense - G. U. Matushansky; G. V. Zavada; Yu. G. Matushanskaya (Moscow Polytechnic University, 2019)
Fundamental changes in the system of training highly qualified personnel in postgraduate studies have actualized the problems of the targets for the functioning of postgraduate studies. The article analyzes the barriers that arise at the stages of training in postgraduate school and preparing for thesis defense. The empirical basis of the work was a survey of the target audience, which resulted in the formation and testing of a questionnaire to assess the impact of barriers on the outcome of postgraduate training and the completion of postgraduate study. The target sample contains three groups: postgraduate students, holders of Candidates of Science degree and Doctors of Science (scientific supervisors) representing higher education and scientific institutions of the Russian Federation. The sample object was 133 people. The results of the experiment were analyzed using statistical graphs method. To identify key barriers to complete postgraduate studies, the construction of the Pareto diagram was used. As a result, we have identified 20% of the most significant barriers impeding postgraduate training and significant barriers to completing the dissertation research. In order to visualize the structure of the barriers, a causal diagram of K. Ishikawa was used. Primary level factors responsible for the result have been identified including a postgraduate student, scientific supervisor, institution and the state. Further, factors of the secondary level in obtaining a positive result of postgraduate training are analyzed. The paper considers the possibility of carrying out some measures to reduce the barriers to successful completion of postgraduate training and Candidate thesis defense. It is noted that such factors as work-study scheme and family life barriers depend on postgraduate student. Higher education institution is also responsible for a number of significant barriers in postgraduate training, in particular the absence of a research reserve. A very powerful, but, unfortunately, rather rare tool for creating a research reserve for postgraduate studies is its integration with the magistracy. We can refer to a British experience of combining master's and doctoral studies by way of example. The article also analyzes the organizational barriers during the periods of thesis preparation and submission as well as barriers relating to supervisor's responsibility. The authors dwell on the problem of low motivation for getting the Candidate of Science degree. It is a common situation in Russia when a Candidate of Science degree holder cannot benefit from the degree obtained. It is necessary to envisage the expansion of positions and professions, where surcharges will be applied for the existing degrees, as well as more comfortable conditions for career growth.